2008
DOI: 10.1152/japplphysiol.00096.2008
|View full text |Cite
|
Sign up to set email alerts
|

Acute moderate-intensity exercise in middle-aged men has neither an anti- nor proinflammatory effect

Abstract: Markovitch D, Tyrrell RM, Thompson D. Acute moderateintensity exercise in middle-aged men has neither an anti-nor proinflammatory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
4
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 44 publications
7
72
4
3
Order By: Relevance
“…Hirose et al (35) stated that the activities that performed resistive eccentric cause a significant increase in serum IL-10. In addition, Markovitch et al (14) and Wilund (36) stated that by increasing physical fitness, concentrations of IL-10 increase; thus, IL-10 has a direct relationship with the fitness that is consistent with the results of the present study. In study of Kasapis and Thompson (37) indicated that some of the beneficial effects of physical activity increase the IL-10 by stimulating anti-inflammatory actions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hirose et al (35) stated that the activities that performed resistive eccentric cause a significant increase in serum IL-10. In addition, Markovitch et al (14) and Wilund (36) stated that by increasing physical fitness, concentrations of IL-10 increase; thus, IL-10 has a direct relationship with the fitness that is consistent with the results of the present study. In study of Kasapis and Thompson (37) indicated that some of the beneficial effects of physical activity increase the IL-10 by stimulating anti-inflammatory actions.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown the inverse relationship between fitness and the amount of lymphocytes and inflammatory markers such as IL-6 and C-reactive protein (CRP), whereas IL-10 has been shown to be positively correlated with fitness. Encouraging the obese individuals, especially children and teens who face with a critical period of their life, to participate in a regular and a desirable sports activity forces the researchers to encourage the people in sports as well as guarantee their health (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com relação ao exercício de baixa intensidade houve uma pequena redução na concentração circulante da IL-6 imediatamente após o exercício, resposta esta, que contradiz prévios achados, que em geral apresentam pequenos incrementos ou nenhum efeito 12,33 do exercício sobre a IL-6.…”
Section: Discussionunclassified
“…It is largely accepted that the expression of IL-6 after acute physical activity do not reach consistent concentrations with short durations or low-to-moderate intensity of training (153) and that routine physical activity determines a decrease of IL-6 levels (instead of IL-10 concentration that is shown to increase). On the other hand, many studies reported data that assess how also low-intensity programs of exercise, such as fast walking (16,27,154,155), could produce a consistent decrease in plasma markers of systemic inflammation although does not determine any enhance in circulating cytokines expression (156). These data allow us to hypothesize that other well-known mechanisms (direct and indirect modulation of the activity of immune cells, neuroendocrine changes induced by exercise, reduced fat mass, for example) could explain a great part of the anti-inflammatory effect of exercise.…”
Section: Conclusive Remarksmentioning
confidence: 99%